The effect of weaving patterns on the impact and bending strength of Eichhornia Crassipes composites for car bumper applications - Muhammad, Arryyanto; Heri, Yudiono; Siregar, Januar Parlaungan; Cionita, Tezara; Deni Fajar Fitriyana, .; Al Ichlas, Imran (Universiti Malaysia Pahang, 2025)
This research focused on Eichhornia Crassipes (water hyacinth) fiber combined with an epoxy matrix to identify the most effective weave pattern that would yield the highest mechanical properties of composites. Composite manufacturing was conducted using the hand lay-up method, consisting of 40% matrix and 60% fiber. The fibers were treated with 20% NaOH for 3 hours. Samples were created with variations of plain, twill, and basket weave patterns, using a car bumper as the control product. The results showed that the highest mechanical strength was found in the twill weave pattern, with an impact value of 0.034 J/mm² and bending of 122.9 MPa, followed by the basket weave pattern with an impact value of 0.030 J/mm² and bending of 90.7 MPa. Each weave pattern exhibited unique characteristics influenced by the number and direction of yarn crossings and interlocking, which in turn affected the composite's mechanical strength. Therefore, the study concludes that composites made from water hyacinth fiber and epoxy resin, particularly with twill and basket weave patterns, have significant potential as competitive substitutes for non-renewable materials in the automotive industry, especially for car bumpers, providing comparable quality in terms of safety and cost. The findings of this research not only aim to enhance the performance of composites reinforced with natural fibers but also address environmental conservation by promoting the use of natural fibers and resource efficiency, aligning with sustainable development goals (SDGs), especially SDG 12 regarding responsible consumption and production.